Effect of imperfect bonding on the dynamic response of a pre-stressed sandwich plate-strip with elastic layers and a piezoelectric core - Daşdemir, Ahmet (Springer Science and Business Media LLC, 2017)
Abstract In this paper, we consider the dynamic response of a pre-stressed sandwich plate-strip with a piezoelectric core and elastic layers under the action of a time-harmonic force resting on a rigid foundation. The investigation is carried out within the framework of the piecewise homogeneous body model by utilizing the exact equations of motion and relations of the linear theory of electro-elasticity. It is assumed that there is a shear-spring-type imperfect contact between the layers, but a complete contact between the plate-strip and the rigid foundation. A mathematical model of the problem is constructed, and the governing equations of motion are solved by employing the finite element method (FEM). Numerical results illustrating the influence of a change in the value of the shear-spring parameter on the dynamic response of the plate-strip are then presented.